Minimum Income Program in the indian village Morro da Saudade in São Paulo, in the Period 2003-2004: analysis of an experience - Fabbri, Elizete Antelmi; Ribeiro, Helena (Saúde e Sociedade, 2007)
The study aimed to analyze the implementation process of the "Programa de Garantia de Renda Familiar Mínima" (PGRMF) Minimum family income program - among the Guarani, an Indian community living in Morro da Saudade, located in a district in the periphery of the city of São Paulo. The research focused on 67 Guarani-Mbya families living in Morro da Saudade and participating in the Program during 2003 and 2004. The qualitative methodology was adopted. The investigation was based mainly on the principles of action research, as well as on the analysis of different sources, official or not. Non-structured interviews enabled to trace back histories and projects of life of the Guarani-Mbya families. Interviews with different actors contributed to the understanding of the impacts. The study revealed that the implementation of PGRMF in the Guarani community living in Morro da Saudade, despite its beneficial aspect of minimizing malnutrition risks, can exacerbate tensions among the groups located at the fringe of the urban area, causing disruptions in their members' health and changing their relationships to the environment. Indian communities still preserve their values based on collectivity and solidarity, incompatible with the features of an Income Distribution Policy suited to the western society. Finally, the study sustains that the Law "Renda Básica de Cidadania"- Citizenship Basic Income - is better suited for Indian groups, if adapted and regulated for them and by them.